Redesigning an Organization of a Construction Company - Andyka Bayu Widiaputra (Syntax Corporation Indonesia, 2023)
The early years of company X were successful, and the company was able to grow into the successful enterprise that it is today. On the other hand, as the company grows, the challenges it faces become more complex, which has led to inefficient operations for the company. The problems stem from company X ineffective business organization as well as its inability to adapt to changing times and circumstances. The problems are showing up in their financial performance, which has shown a drop in revenue, which has stopped the company from growing. Internal observation will be used in this study to help figure out what the real problems are and what company X should do next. The 7S McKinsey model will be used to figure out what needs to be changed in terms of reorganization. We will look at the organization's strategy, structure, system, style, people, skills, and shared values. Seven company X employees were interviewed, and after the interview results are coded it was shown that their desire for the 7S is not align with the company's current state, which shows that the company needs to change. Lewin's Three Stages of Change model is used to redesign organizations once the change that was wanted has taken place. It will be used to figure out what steps company X should take to change their organization in a way that will work, starting with unfreezing, then making changes, and ending with freezing the transformation of the organization